Anylasis of Nail Bed Injuries: Cause, Outcome, Treatment. Issue 2 (August 2021) - Gu, Ja Hea; Choi, Su Hyun; Yoon, Jae Hee
Abstract : Background: Although fingertip and nail bed injuries have a high incidence, appropriate management of nail bed injuries remains controversial. This study is the completion of data derived from nail bed injuries with follow-up of a minimum of 6 months to suggest an appropriate treatment. Methods: In the retrospective study, we analyzed data from 549 nail bed injuries for 6 years and age, type of injury, fractures, treatment methods, and outcomes were reviewed. Results were determined and these were divided to identical to the opposite group, abnormalities based on Zook criteria. Statistical analysis was done according to injury category (type, site, nail substitute, and fracture) and overall final grade. Results: Over 50% (293 cases) had excellent results. Rates of very good, good, fair, and poor results were 22.6%, 11.3%, 6.2%, and 6.6%, respectively. Poorer results were obtained for fold injuries, crush, and avulsive injuries. The presence of a fracture was associated with poor results. Conclusions: The cause of poor results is thought to be multifactorial. Although, overall outcomes were good, nail splitting, nail roughness, and nail adherence can cause dirtiness, catching, bending, and various cosmetic problems. Thus, careful suture and replacement of nail to nail fold are important to reach good results.